PENGARUH POTENSI PENERIMAAN PAJAK DAN RETRIBUSI TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA SERANG: : PENGARUH POTENSI PENERIMAAN PAJAK DAN RETRIBUSI TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA SERANG - Anis Masyruroh Masyruroh (Jurnal Kebijakan Pembangunan Daerah, 2021)
One of the sources of local revenue is taxes and levies, because they have a very important role in government administration, both in development and in improving the community. This study aims 1). To determine the effect of taxes on increasing Serang City Original Revenue, 2) To determine the effect of levies on increasing Serang City Local Revenue. 2). 3) To determine the effect of levies and local taxes on increasing Serang City Original Regional Revenue. The data of this research are time series data. The data used are secondary data from 2015 to 2019. The research method uses the causative method, which is a study that analyzes the effect of the dependent variable and the independent variable. Data analysis in this study using multiple linear regression analysis. The results showed that 1) Retribution has an effect on the increase in Serang City Local Revenue because the Sig value is 0.008 <from 0.05, 2) Local Taxes have an effect on the increase in Regional Original Revenue in Serang City because the Sig value is 0.027 <from 0.05, 3 ) Regional Levies and Local Taxes together have an effect on the increase in Serang City's Original Revenue because the value of the Sig. 0.047 <of 0.05.